Manual de políticas de calidad ISO 9001:2015 en la empresa Reyursa S.A., ciudad de Machala. - Salazar Tubetano, Betsy Janellis (My University, 2018)
A quality management system to be implemented in a company provides benefits to the competitiveness in the market, performing improvements in each area of the entity, providing commitment, dynamism and responsibility of workers through efficient internal and external processes of the organization , therefore, this work aims to develop a Manual of Quality Policies ISO 9001: 2015 in the company Reyursa SA located in the city of Machala, the development of the manual contributes to the development of quality of the company, with greater business opportunities in the market, management of policies or feasible regulations for a continuous improvement in each administrative and operational process, the Management System of Quality, takes as reference all aspects and procedures of the ISO 9001: 2015 standard. The methodological application is based on the interview with the administrative manager and document review of the ISO 9001: 2015 Standard, the results explain the need to implement a standardized Quality Management System for the company's departments as well as the collaborators in improving their Labor conditions. The interview shows the managerial interest of adapting the standards to the internal and external processes of the organization, with the need to improve the functions on the part of the collaborators. The theoretical contribution bases representative bases to establish the advantages of certifying a Quality Standard and guaranteeing a quality product.
Un sistema de gestión de calidad al ser implementada en una empresa proporciona beneficios a la competitividad en el mercado, desempeñando mejoras en cada área de la entidad, aportando compromiso, dinamismo y responsabilidad de los trabajadores a través de eficientes procesos internos y externos de la organización, por ende el presente trabajo tiene como objetivo elaborar un Manual de Políticas de Calidad ISO 9001:2015 en la empresa Reyursa S.A. ubicada en la Ciudad de Machala, la elaboración del manual contribuye al desarrollo de calidad de la empresa, con mayores oportunidades de negocio en el mercado, manejo de políticas o normativas factibles para una mejora continua en cada proceso administrativo y operacional, el Sistema de Gestión de la Calidad, toma como referencia todos los aspectos y procedimientos de la norma ISO 9001:2015. La aplicación metodológica se basa en la entrevista al gerente administrativo y revisión documental de la Normativa ISO 9001:2015, los resultados explican la necesidad de implementar un Sistema de Gestión de la Calidad estandarizado a los departamentos de la empresa así como los colaboradores en mejorar sus condiciones laborales. La entrevista muestra el interés gerencial de adaptar las normas a los procesos internos y externos de la organización, con la necesidad de mejorar las funciones por parte de los colaboradores. El aporte teórico fundamenta bases representativas para establecer ventajas de certificar una Norma de calidad y garantizar un producto de calidad.
Keywords: SISTEMA DE GESTIÓN DE LA CALIDAD; MANUAL DE POLÍTICAS; CERTIFICACIÓN; ISO 9001:2015